Depression, anxiety, psychotropic drugs, and acute myocardial infarction: large prospective study of United Kingdom women. Issue 4 (10th March 2023) - Parkin, Lianne; Balkwill, Angela; Green, Jane; Reeves, Gillian K.; Beral, Valerie; Floud, Sarah
Abstract: Background: Reported associations between depression and myocardial infarction in some studies might be explained by use of psychotropic drugs, residual confounding, and/or reverse causation (whereby heart disease precedes depression). We investigated these hypotheses in a large prospective study of UK women with no previous vascular disease. Methods: At baseline in median year 2001 (IQR 2001–2003), Million Women Study participants reported whether or not they were currently being treated for depression or anxiety, their self-rated health, and medication use during the previous 4 weeks. Follow-up was through linkage to national hospital admission and mortality databases. Cox regression yielded adjusted hazard ratios (aHRs) and 95% confidence intervals (CIs) for the first myocardial infarction event in those reporting treatment for depression or anxiety (subdivided by whether or not the treatment was with psychotropic drugs) v. not, and stratified by self-reported health and length of follow-up. Results: During mean follow-up of 13.9 years of 690 335 women (mean age 59.8 years) with no prior heart disease, stroke, transient ischaemic attack, or cancer, 12 819 had a first hospital admission or death from myocardial infarction. The aHRs for those reporting treatment for depression or anxiety with, and without, regular use of psychotropic drugs were 0.96 (95% CI 0.89–1.03) and 0.99 (0.89–1.11), respectively. No associations were found separately in women who reported being in good/excellent or poor/fair health or by length of follow-up. Conclusion: The null findings in this large prospective study are consistent with depression not being an independent risk factor for myocardial infarction.